Towards Clinically Available Closed-loop Systems for Mechanical Ventilation in the Intensive Care Unit - Tschopp, M.; Lovis, C. (Yearbook of Medical Informatics, 2009)
Objective To provide an overview of the state-of-the-art of closedloop systems in the field of mechanical ventilation.Methods This survey is reviewing the literature and proposes an overview of existing closed-loop systems, in different areas of mechanical ventilation. It discusses the key points that guided their development and addresses specific issues such as their performance and penetration at the bedside.Results Much research has been undertaken in the hope of improving patient-ventilator interaction and shortening the weaning process. This led to the development of new modes of ventilation and expert weaning systems that are starting to achieve a wider clinical audience.Conclusion Intensive care unit personnel are facing increasing work load during care for patients with severe, multi-system illness, using sophisticated equipments that generate high information flows requiring quick processing. Mechanical ventilation is a good example of a process that requires skilful and timely management of multiple parameters that could be delegated to closed-loop systems. Availability of commercial offerings, validated by randomized controlled trials in a well-defined set of clinical situations, is starting to fulfill the promise of intelligent systems skillfully assisting caregivers at the bedside.
Keywords: Mechanical ventilation; closed-loop; weaning; ICU